1984
DOI: 10.1111/j.1095-8312.1984.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection by passerine birds is anti-apostatic at high prey density

Abstract: Most of the results from past experiments with wild birds and green and brown pastry ‘baits’ have suggested that disproportionately more of the rare forms are eaten when bait density is high (i.e. selection is anti‐apostatic). In two separate series of experiments we presented birds with dishes containing 270 baits of one colour and 30 of another. In series I, five different pairs of colours were presented simultaneously to wild birds at two sites. One colour of each pair was common at one site and the same co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Experiments with artificial pastry prey have shown that wild birds tend to remove disproportionately more common forms when prey density is low while at very high densities they tend to eat disproportionately more rare forms (Allen 1972(Allen , 1976Horsley et al 1979;Allen and Anderson 1984;Church et al 1997). The evolutionary consequences of such selection on real prey would be to promote polymorphism within populations at low density and monomorphism when the density is much higher (Clarke 1962;Greenwood 1984Greenwood , 1985.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with artificial pastry prey have shown that wild birds tend to remove disproportionately more common forms when prey density is low while at very high densities they tend to eat disproportionately more rare forms (Allen 1972(Allen , 1976Horsley et al 1979;Allen and Anderson 1984;Church et al 1997). The evolutionary consequences of such selection on real prey would be to promote polymorphism within populations at low density and monomorphism when the density is much higher (Clarke 1962;Greenwood 1984Greenwood , 1985.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, when the`baits' are presented at very high density (410 000 m 72 ), they remove disproportionately more of the rare form (Allen 1972;Horsley et al 1979;Allen & Anderson 1984). Thus, the selection by wild birds is frequency dependent and its direction is in£uenced by prey density.…”
Section: Introductionmentioning
confidence: 99%
“…One possible cause of anti-apostatic selection is that individual predators tend to remove rare forms because they stand out from the background of the rest (Allen 1972). Another possible cause of anti-apostatic selection at the population level is from variability in frequency-independent selection among individual predators (P. Chesson 1984;Sherratt & MacDougall 1995), and there is some evidence for such variability from the behaviour of wild blackbirds feeding on pastry prey at very high density (Allen & Anderson 1984).…”
Section: Introductionmentioning
confidence: 99%
“…1a), following the techniques of Allen et al (1990), Allen and Anderson (1984) and Greenwood et al (1984). In the``aggregated'' treatments, the prey were arranged into ®ve high-density clumps (one in the centre and one near to each corner), with a frequency of 9:1 (18:2) present in each clump (Fig.…”
Section: Methodsmentioning
confidence: 99%